The Enhancement of Teacher Creativity Through School Climate, Servant Leadership, and Scientific Literacy - Fabiana, Fabiana (UNIVERSITAS PAKUAN, 2019)
The purpose of this study was to empirically determine the increase in teacher creativity by looking at the influence on school climate, servant leadership, and scientific literacy and to identify ways to increase teacher creativity in the Bogor District. The total sample of the study consisted of 111 teachers who were randomized using a proportional random sampling technique from 152 teachers. The method used is a quantitative method with path analysis. The results showed: 1) there is a direct effect of the school climate on teacher creativity, which is significant with the value of the path coefficient (βy1= 0.178); 2) there is a direct effect of servant leadership on teacher creativity, which is significant with the path coefficient value (βy2 = 0.233); 3) there is a direct effect of scientific literacy on teachers' creativity, which is significant with the path coefficient value (βy3 = 0.584); 4) there is a direct effect of school climate on science literacy that is significant with the path coefficient value (βx3x1 = 0.319); 5) there is a direct effect of servant leadership on teacher creativity, which is significant with the value of the path coefficient (βx3x2 = 0,446) .